Comments on a Method to Measure Sucralose Using UV Photodegradation Followed by UV Spectrophotometry. (22nd November 2019) - Fang, Te; Andrews, Susan A; Hofmann, Ron
Abstract: A simple and quick method to measure sucralose in aqueous solution at concentrations in the order of 0.1–1.2 g·L −1 proposed by Idris et al. uses UV irradiation prior to UV spectrophotometry. The photolysis of sucralose forms a photoactive compound characterized by maximum absorbance at approximately 270 nm. The conditions required for sucralose photolysis, however, had not been completely reported. In this work, the procedure described by Idris et al. was replicated using a low-pressure UV lamp to irradiate sucralose samples with a wider range of initial concentrations(0.04–10 g·L −1 ) with known fluences. It was determined that care must be taken to ensure that the same fluence is applied for both calibration and measurement steps because the absorbance of the sucralose photolysis product is a function of the applied fluence. The way thesamples are irradiated also has an impact on the results in that the method exhibits a greater linear range if an apparatus is used that maximizes the fluence rate (e.g., by placing samples closer to the UV source or using a higher-intensity lamp).